2020
DOI: 10.21203/rs.3.rs-113057/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vortex Simulation of Two Cylinders in Tandem Using Overlapping Grid System

Abstract: To give a considerable time reduction in the calculation of the vortex velocity and in the CPU time, discrete vortex modelling of flows using overlapping grid system for two tandem cylinders is carried out. This simple and time efficient method gives a better scatter of surface vorticity as the vortices around the body are now calculated on grid point. This research is to simulate the loading on structural elements of the structures due to their interaction with anodes or with other members. To show the flow p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Pemanfaatan NBM sebagai standar informasi memberikan dampak positif dalam menghitung dan menganalisis tingkat ketahanan pangan di Indonesia. Dengan demikian, data perubahan harga komoditas pangan strategis bukan hanya memberikan wawasan tentang kondisi ekonomi, tetapi juga memberikan dasar yang kuat untuk pengambilan keputusan dan perencanaan kebijakan di tingkat nasional (Mardianto, E., & Wardhana, K. 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…Pemanfaatan NBM sebagai standar informasi memberikan dampak positif dalam menghitung dan menganalisis tingkat ketahanan pangan di Indonesia. Dengan demikian, data perubahan harga komoditas pangan strategis bukan hanya memberikan wawasan tentang kondisi ekonomi, tetapi juga memberikan dasar yang kuat untuk pengambilan keputusan dan perencanaan kebijakan di tingkat nasional (Mardianto, E., & Wardhana, K. 2020).…”
Section: Hasil Dan Pembahasanunclassified
“…50% protection [5] Sepsis Case-control study Reduced childhood mortality; better long-term survival [6] Cutaneous malignant melanoma Case-cohort study No strong beneficial effect [7] Pneumonia and sepsis Randomized controlled trials 43% reduction in infectious disease mortality; 38% reduction within neonatal period [8] Respiratory tract infections Data analysis based on Demographic and Health Surveys data 17% to 37% risk in reduction [9] Elderly pneumonia Clinical trials The risk of pneumonia was significantly decreased [10] Acute URTIs respiratory tract infection Humans Protective effect on URTIs [11] Acute lower respiratory tract infection (ALRI) Infants BCG vaccination may have a non-targeted protective effect against ALRI [12] Leishmania amazonensis Humans A strong association between the increase of the frequency of innate immune system cells and the healing of lesions [13] Influenza virus Human study…”
Section: Cross-protectionmentioning
confidence: 99%
“…Therefore, BCG vaccination protects consistently from subsequent infections [65]. In a small study in Indonesia, multiple doses of BCG vaccination in elderly people exhibited a significant reduction in the number of respiratory tract virus infections as compared with a placebo [66]. Another clinical trial in Japan found that BCG vaccination in people makes them less susceptible to pneumonia [67].…”
Section: Modulation Of the Immune Response To A Virus 41 Immunogenic Response Training To Develop Immunity Reduce Susceptibility And The mentioning
confidence: 99%